2012
DOI: 10.1002/path.3982
|View full text |Cite
|
Sign up to set email alerts
|

Non‐junctional human desmoglein 3 acts as an upstream regulator of Src in E‐cadherin adhesion, a pathway possibly involved in the pathogenesis of pemphigus vulgaris

Abstract: E-cadherin, a classical cadherin, is an adhesion receptor in adherens junctions and has important functions in cell-cell adhesion and cell signalling. Recently we reported that a desmosomal cadherin, desmoglein 3 (Dsg3), an autoantigen in pemphigus vulgaris (PV), associates with E-cadherin and activates Src, which results in tyrosine phosphorylation of adherens junction proteins. However, the nature of such an interaction and its role in cell-cell adhesion remain unclear. In this report, we provide direct evid… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

12
90
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 58 publications
(103 citation statements)
references
References 67 publications
12
90
0
1
Order By: Relevance
“…In some cases, a specifi c signaling molecule associates with the Dsg3 complex. This has been shown for Rho GTPases and Src (Tsang et al, 2012a(Tsang et al, , 2012b. PKC has been located at the desmosomal plaque via electron microscopy (Garrod et al, 2005), and may directly bind to desmosomal proteins.…”
Section: Signaling Function Of Desmosomal Cadherinsmentioning
confidence: 81%
See 1 more Smart Citation
“…In some cases, a specifi c signaling molecule associates with the Dsg3 complex. This has been shown for Rho GTPases and Src (Tsang et al, 2012a(Tsang et al, , 2012b. PKC has been located at the desmosomal plaque via electron microscopy (Garrod et al, 2005), and may directly bind to desmosomal proteins.…”
Section: Signaling Function Of Desmosomal Cadherinsmentioning
confidence: 81%
“…Rho GTPases act as molecular switches in actin dynamics (Gliem et al, 2010;Waschke et al, 2006). The involvement of p38MAPK is well established, which may require its downstream kinase MAPKAP kinase 2 (MK2) (Berkowitz et al, 2005(Berkowitz et al, , 2006Mao et al, 2013) and epidermal growth factor receptor (EGF-R) and/or Src signaling (Bektas et al, 2013;Chernyavsky et al, 2007;Frusic-Zlotkin et al, 2006;Tsang et al, 2012b). Other molecules implicated in pemphigus are Akt/mTOR and FAK (Gil et al, 2012;Pretel et al, 2009) as well as JNK (Marchenko et al, 2010), CDK-2 (Lanza et al, 2008), PERP (Nguyen et al, 2009) and factors associated with apoptotic signaling such as caspases 3, 6, 8, and 9 as well as Bcl/Bax and others (Li et al, 2009;Marchenko et al, 2010).…”
Section: Role Of Signaling Induced By Autoantibodies In Pemphigus Patmentioning
confidence: 99%
“…164 A recent study suggested that Pkp2 is also involved in the regulation of apoptosis. 165 Furthermore, reexpression of Dsp in cells with an epigenetic inactivation of the Dsp gene exhibited an increased sensitivity to apoptosis by the upregulation of Pg and the concomitant inhibition of β-catenin -TCF/ LEF-dependent transcription.…”
mentioning
confidence: 99%
“…All desmosomal cadherin isoforms are expressed in the human epidermis in a layer-and differentiation-dependent manner. In the human epidermis, beside building the core of desmosomes, the desmosomal cadherins are also supposed to be present in the cell membrane outside of desmosomes (3,4), whereas the expression of the anchoring protein DP is restricted to desmosomes. The relevance of adhesion mediated by desmosomal cadherins is illustrated by the autoimmune blistering skin disease pemphigus vulgaris.…”
mentioning
confidence: 99%
“…phosphorylated, p38 MAPK (p-p38 MAPK), which established a link between p38 MAPK activation and loss of Dsg3 interaction in pemphigus vulgaris (20). Furthermore, Dsg3, via interaction with E-cadherin, has been demonstrated to be involved in Src signaling (3,21).…”
mentioning
confidence: 99%